PENGARUH SIKAP, NORMA SUBJEKTIF DAN KONTROL PERILAKU TERHADAP INTENSI KEWIRAUSAHAAN MAHASISWA (Studi Pada Mahasiswa Universitas Widya Dharma Klaten) - Nursito, Sarwono; Prasetyo, Jarot; Haris, Abdul; Hadi, Abdul (FAKULTAS EKONOMI DAN PSIKOLOGI UNWIDHA KLATEN, 2023)
Educated youths play a crucial role and contribute significantly to the economy. Thus, it is urgent to develop entrepreneurial activities among educated youth, especially university students. Therefore, this study aims to examine the effect of attitudes toward entrepreneurship, subjective norms, and behavioral control on entrepreneurial intentions among college students. This research is a survey involving 150 students from Widya Dharma University, Klaten, and uses a purposive sampling method as a sampling technique. The collected data were then analyzed using multiple linear regression analysis. The results show that attitudes toward entrepreneurship, subjective norms, and behavioral control have a positive and significant effect, both partially and simultaneously, on students' entrepreneurial intentions.performance.